(untitled) (Economics and region, 2018)
In order to determine the strategic guidelines for the development of the domestic market of goods, it is necessary to form a subsystem of the information base, which is intended for its research and takes place under the condition of commodity-money relations. Such conditions reflect the state of the infrastructure, the degree of state intervention and the competitive conditions that take place in the domestic market. The purpose of the study is a comprehensive analytical study of the main elements of the infrastructure of the domestic market of goods, forming a subsystem of the information base for the development of the domestic market. Main material and results. The development of transport, warehousing and communication (postal and courier activities) is very important for the development of the internal market of goods. As the research showed (in general for 2008-2017) the number of transport, warehousing, postal and courier activities decreased by 0.66%. Regarding the length of highways, it also decreased by 3.77%. The area of warehouses decreased by 55.33% over the period under study, which was observed in early 2008. Of great importance for the development of the domestic market are financial and insurance companies. The number of enterprises of financial and insurance activities (taking into account the number of banks) decreased by 32.11%. Professional, scientific and technical activities can significantly improve the efficiency of the functioning of the domestic market, but also decreased by 27.74%. Companies operating in the field of administrative and auxiliary services play an important role for the development of the domestic commodity market. The number of enterprises in the area of administrative and auxiliary services in 2008-2017 has decreased by 2,464 units or by 15.16%. Thus, for most indicators of the development of the infrastructure of the domestic market, it was observed, though insignificant, but deteriorating. Although markets with a competitive structure are the most important element in the structure of Ukrainian markets, their share decreased over the period by 15.2%. Instead, the share of markets with rigid oligopoly and monopolized markets has increased. Research results. The regulatory influence of the state in 2008-2017 was stimulating on the development of all components of the national economy, including the development of the domestic market of goods. The performed calculations allow us to confirm the need for the formation of an information base. Thanks to the research, it becomes possible to present the collected information in the most favorable form for further research and to simplify the procedure for assessing the development of the domestic market of goods.